Heterotic strings on T 3/ℤ2, Nikulin involutions and M-theory - Samir Acharya, Bobby; Aldazabal, Gerardo Marcelo; Font, Anamaría; Narain, Kumar; Zadeh, Ida G. (Springer, 2022)
Fil: Samir Acharya, Bobby. Kings College London (kcl); . The Abdus Salam. International Centre for Theoretical Physics; Italia